(untitled) (Bangladesh Journal of Neuroscience, 2019)
Background: Migraine headache is one of the commonest cause of primary headache. This study aims to reveal the clinical profile of migraine headache in Bangladeshi people presented in Headache clinic, Dhaka Medical College Hospital. It will give an overview on presentation of migraine and its functional consequences among the people of Bangladesh. Methods: The study was a hospital based cross sectional observational study. It was conducted in the Headache clinic Dhaka Medical college Hospital from January 2018 to December 2018. About 854 patients with headache was attended in the headache clinic during the study period. Of that 234 patients were diagnosed as migraine according to ICHD-3 classification and 75 patents were enrolled in this study by systematic sampling. Details were collected using a preformed questioner. Results: In this study migraine burden among the headache patients found to be about 25%.The mean age of the onset of the migraine headache in this study was found to be 25.2±11.86 years, in most of the cases (4 68%) in 15-34 years age group. In this study 36% of the patient with migraine had positive family history which is significantly higher in patients with migraine with aura (52% vs. 30% p value <0.5). In this study about 81% of the patient has single or multiple trigger factors. Along with other known factor sun exposure and journey was found to be the important trigger factors for Bangladeshi population. In this study 22% of the female migraineurs and 33% of male migraineurs had aura. About 53% of the patient with aura had combinations of aura and 47% patient had exclusive visual aura. In the present study 100% of the patient had visual aura, 42% had brainstem aura and 10% had sensory aura. The study revealed that 25% patient had chronic daily headache due to migraine, 26% patient had >5 attack/ month and 15% patient had < 4 attack per month. In this study 44% had moderate headache and 56% had severe headache according to VAS score. Chronic migraine with anxiety, chronic migraine with medication overuse Migralepsy, Status migrainosus were found as a complications of migraine in this study. According to MIDAS score Patient largely had Mild (32%) to Moderate (34.67%) disability. Conclusions: Clinical profile of migraine in Bangladesh differs in some trigger points and migraine subtypes than the western world. Sun exposure and journey found to be most important triggers. Migraine with brainstem aura occurs in a significant number of the patient. Bangladesh Journal of Neuroscience 2019; Vol. 35 (1): 1-9